Extracellular vesicles from gastric epithelial GES-1 cells infected with Helicobacter pylori promote changes in recipient cells associated with malignancy - González, María Fernanda; Burgos-Ravanal, Renato; Shao, Baohai; Heinecke, Jay; Valenzuela-Valderrama, Manuel; Corvalán, Alejandro H.; Quest, Andrew F. G. (Frontiers in Oncology, 2022)
Chronic Helicobacter pylori (H. pylori) infection is considered the main risk factor for the development of gastric cancer. Pathophysiological changes in the gastric mucosa initiated by this bacterium can persist even after pharmacological eradication and are likely attributable also to changes induced in non-infected cells as a consequence of intercellular communication via extracellular vesicles (EVs). To better understand what such changes might entail, we isolated EVs from immortalized normal gastric GES-1 cells infected (EVHp+) or not with H. pylori (EVHp-) by ultracentrifugation and characterized them. Infection of GES-1 cells with H. pylori significantly increased the release of EVs and slightly decreased the EV mean size. Incubation with EVHp+ for 24 h decreased the viability of GES-1 cells, but increased the levels of IL-23 in GES-1 cells, as well as the migration of GES-1 and gastric cancer AGS cells. Furthermore, incubation of GES-1 and AGS cells with EVHp+, but not with EVHp-, promoted cell invasion and trans-endothelial migration in vitro. Moreover, stimulation of endothelial EA.hy926 cells for 16 h with EVHp+ promoted the formation of linked networks. Finally, analysis by mass spectrometry identified proteins uniquely present and others enriched in EVHp+ compared to EVHp-, several of which are known targets of hypoxia induced factor-1 (HIF-1) that may promote the acquisition of traits important for the genesis/progression of gastric pre-neoplastic changes associated with H. pylori infection. In conclusion, the harmful effects of H. pylori infection associated with the development of gastric malignancies may spread via EVs to non-infected areas in the early and later stages of gastric carcinogenesis.